Hot-melt waterproof glue for optical cable and preparation method of hot-melt waterproof glue

By refining the formulation and modifying the process of hot-melt waterproof adhesive, the problems of insufficient voltage breakdown resistance and impact resistance of waterproof adhesives for optical cables have been solved, achieving multi-functional protection and improved stability of optical cables.

CN119286433APending Publication Date: 2025-01-10SHANGHAI HONGHUI OPTICS COMM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531243.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing waterproof adhesives for optical cables have weak resistance to voltage breakdown and impact, and external factors can easily affect the normal use of optical cables.

Method used

The hot-melt waterproof adhesive is formulated with rubber, modified rosin resin, polymethyltriethoxysilane, filler, stearic acid, carbon black, antioxidant and nanocrystalline cellulose. The wettability and adhesion of the waterproof adhesive are improved through modification of the modified rosin resin and preparation by a specific process.

Benefits of technology

It improves the waterproof, moisture-proof, insulation, and voltage breakdown resistance of optical cables, enhances their impact resistance, extends their service life, and ensures the stability and security of power and digital information transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286433A_ABST
    Figure CN119286433A_ABST
Patent Text Reader

Abstract

The invention discloses a hot-melt waterproof adhesive for optical cables and a preparation method thereof, and relates to the technical field of waterproof adhesives, the hot-melt waterproof adhesive is prepared from the following components: rubber, modified rosin resin, polymethyltriethoxysilane, a filler, stearic acid, carbon black, polybutylene adipate, an antioxidant and nanocrystalline cellulose; the waterproof glue with the sealing function is designed for the optical cable, belongs to hot-melt filling waterproof glue, and can play a plurality of functions of water resistance, moisture resistance, insulation, voltage breakdown resistance and the like for the optical cable after being filled into the optical cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waterproof adhesives, in particular to a hot-melt waterproof adhesive for optical cables. Background Art

[0002] Optical cables can form an optical network, which can integrate power grid, information network, sensor network, metering network, protection network, control network, video network, etc. Therefore, optical cables and optical networks can create a new industry and new field, and its application will surely promote the rapid development of industries such as smart grid and new energy.

[0003] The working environment of optical cables is relatively complex. Therefore, they need to have excellent waterproof and impact-resistant properties to extend their working life and avoid damage to optical cables caused by external factors, which may cause interruption of information and power transmission and affect the stable operation of the optical network.

[0004] In order to improve the performance of optical cables, waterproof glue is filled in the optical cables to improve their waterproof performance. However, the waterproof glue prepared by the prior art has general resistance to voltage breakdown and relatively weak impact resistance. External factors can easily affect the normal use of optical cables.

[0005] Based on this, a hot-melt waterproof adhesive for optical cables is provided to solve the existing technical problems. Summary of the invention

[0006] The purpose of the present invention is to provide a hot-melt waterproof adhesive for optical cables and a preparation method thereof, so as to solve the deficiencies in the prior art.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A hot-melt waterproof adhesive for optical cables comprises the following ingredients by weight: 60-85 parts of rubber, 10-12 parts of modified rosin resin, 1-3 parts of polymethyltriethoxysilane, 15-18 parts of filler, 1-2 parts of stearic acid, 5-8 parts of carbon black, 1-1.5 parts of polybutylene adipate, 1-1.2 parts of antioxidant and 2-3 parts of nano-microcrystalline cellulose.

[0009] As a further technical solution, the modified rosin resin preparation method is:

[0010] Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber;

[0011] Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution;

[0012] Among them, the stirring speed is 200r / min;

[0013] The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion.

[0014] Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40;

[0015] Among them, the frequency of ultrasonic dispersion is 60kHz;

[0016] The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

[0017] As a further technical solution, the activated fiber preparation method is:

[0018] Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution;

[0019] The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber;

[0020] Wherein, the immersion temperature is 50°C;

[0021] The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 50-55 minutes, then taken out of the furnace and cooled to room temperature.

[0022] As a further technical solution, the mass fraction of the potassium hydroxide solution is 10%;

[0023] The mixing ratio of phenolic fiber and potassium hydroxide solution is 10-12g:100mL.

[0024] As a further technical solution: the heating rate is 10°C / min;

[0025] The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

[0026] As a further technical solution, the mixing ratio of the rosin resin and the organic solvent is 30-40 g: 200 mL;

[0027] The organic solvent is toluene.

[0028] As a further technical solution: the filler is calcium carbonate;

[0029] The antioxidant is antioxidant 1010;

[0030] The rubber is butyl rubber.

[0031] A method for preparing a hot-melt waterproof adhesive for an optical cable comprises the following steps:

[0032] S1 Preparation:

[0033] Weigh the components according to the mass ratio: rubber, modified rosin resin, polymethyltriethoxysilane, filler, stearic acid, carbon black, polybutylene adipate, antioxidant, nano-microcrystalline cellulose;

[0034] S2 Melting:

[0035] The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid;

[0036] S3 Mixing:

[0037] Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

[0038] As a further technical solution: the stirring speed is 500r / min.

[0039] Beneficial effects:

[0040] The present invention is a waterproof adhesive with sealing function designed for optical cables. It is a hot-melt filling waterproof adhesive. After being filled into the interior of the optical cable, it can play multiple functions for the optical cable, such as waterproofing, moisture-proofing, insulation, and voltage breakdown resistance.

[0041] During the construction process, the prepared waterproof glue is heated to make it fluid, so that it can be more easily injected into the interior of the optical cable and is easy to process. The present invention introduces modified rosin resin into the water-releasing glue, and through its characteristics, the wettability of the waterproof glue can be improved. Therefore, when the waterproof glue is used to fill the interior of the optical cable, the optical cable core can be quickly and fully wrapped and moistened, and various gaps can be filled and the air in the gaps can be discharged, thereby greatly reducing the possibility of subsequent water vapor penetration.

[0042] The optical cable filled with the waterproof glue prepared by the present invention can not only better cope with the corrosion erosion of various corrosion factors, but also has excellent impact resistance after solidification, can cope with a variety of impacts, and has a sufficient protective effect on the optical cable core.

[0043] The waterproof adhesive prepared by the invention through the coordination of various components has good high and low temperature resistance and excellent oxidation resistance, thereby prolonging the service life of the optical cable.

[0044] When the optical cable is filled with the waterproof glue prepared by the present invention and cured, the buffering performance of the waterproof glue after curing can be improved due to the effect of the modified rosin resin, so that it can cope with various stress impacts, greatly reduce the stress damage to the optical cable caused by stress impacts, and improve its protective effect on the optical cable core.

[0045] The waterproof glue prepared by the invention has excellent insulation and dielectric properties and is suitable for filling of most optical cables.

[0046] The waterproof adhesive prepared by the present invention has a relatively low system viscosity after hot melting, has good wettability with metal impregnation, and can better fill and wet the optical cable core.

[0047] Through the synergistic effect of modified rosin resin and butyl rubber, the waterproof adhesive has excellent bonding strength and can be tightly combined with the optical cable sheath and optical cable core, fully ensuring the stability, reliability and safety of optical cables for power and digital information transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a statistical diagram of the breakdown voltage of each test group. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] A method for preparing a hot-melt waterproof adhesive for an optical cable comprises the following steps:

[0052] S1 Preparation:

[0053] Weigh the following components according to the mass ratio: 75 parts of butyl rubber, 10 parts of modified rosin resin, 1 part of polymethyltriethoxysilane, 15 parts of filler, 1 part of stearic acid, 5 parts of carbon black, 1 part of polybutylene adipate, 1 part of antioxidant, and 2 parts of nano-microcrystalline cellulose.

[0054] The preparation method of modified rosin resin is as follows:

[0055] Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber;

[0056] Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution;

[0057] Among them, the stirring speed is 200r / min;

[0058] The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion.

[0059] Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40;

[0060] Among them, the frequency of ultrasonic dispersion is 60kHz;

[0061] The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

[0062] The activated fiber preparation method is:

[0063] Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution;

[0064] The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber;

[0065] Wherein, the immersion temperature is 50°C;

[0066] The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 50 minutes, then taken out of the furnace and cooled to room temperature.

[0067] The mass fraction of potassium hydroxide solution is 10%;

[0068] The mixing ratio of phenolic fiber and potassium hydroxide solution is 10g:100mL.

[0069] The heating rate is 10℃ / min;

[0070] The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

[0071] The mixing ratio of rosin resin and organic solvent is 30g:200mL;

[0072] The organic solvent is toluene.

[0073] The filler is calcium carbonate;

[0074] The antioxidant is antioxidant 1010;

[0075] S2 Melting:

[0076] The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid;

[0077] S3 Mixing:

[0078] Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

[0079] The stirring speed is 500r / min.

[0080] Example 2

[0081] A method for preparing a hot-melt waterproof adhesive for an optical cable comprises the following steps:

[0082] S1 Preparation:

[0083] Weigh the following components according to the mass ratio: 76 parts of butyl rubber, 11 parts of modified rosin resin, 2 parts of polymethyltriethoxysilane, 16 parts of filler, 1.5 parts of stearic acid, 6 parts of carbon black, 1.2 parts of polybutylene adipate, 1 part of antioxidant, and 2.2 parts of nano-microcrystalline cellulose.

[0084] The preparation method of modified rosin resin is as follows:

[0085] Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber;

[0086] Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution;

[0087] Among them, the stirring speed is 200r / min;

[0088] The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion.

[0089] Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40;

[0090] Among them, the frequency of ultrasonic dispersion is 60kHz;

[0091] The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

[0092] The activated fiber preparation method is:

[0093] Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution;

[0094] The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber;

[0095] Wherein, the immersion temperature is 50°C;

[0096] The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 52 minutes, then taken out of the furnace and cooled to room temperature.

[0097] The mass fraction of potassium hydroxide solution is 10%;

[0098] The mixing ratio of phenolic fiber and potassium hydroxide solution is 11g:100mL.

[0099] The heating rate is 10℃ / min;

[0100] The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

[0101] The mixing ratio of rosin resin and organic solvent is 35g:200mL;

[0102] The organic solvent is toluene.

[0103] The filler is calcium carbonate;

[0104] The antioxidant is antioxidant 1010;

[0105] S2 Melting:

[0106] The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid;

[0107] S3 Mixing:

[0108] Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

[0109] The stirring speed is 500r / min.

[0110] Example 3

[0111] A method for preparing a hot-melt waterproof adhesive for an optical cable comprises the following steps:

[0112] S1 Preparation:

[0113] Weigh the following components according to the mass ratio: 78 parts of butyl rubber, 11 parts of modified rosin resin, 2 parts of polymethyltriethoxysilane, 16 parts of filler, 1.5 parts of stearic acid, 6 parts of carbon black, 1.2 parts of polybutylene adipate, 1.2 parts of antioxidant, and 2 parts of nano-microcrystalline cellulose.

[0114] The preparation method of modified rosin resin is as follows:

[0115] Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber;

[0116] Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution;

[0117] Among them, the stirring speed is 200r / min;

[0118] The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion.

[0119] Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40;

[0120] Among them, the frequency of ultrasonic dispersion is 60kHz;

[0121] The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

[0122] The activated fiber preparation method is:

[0123] Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution;

[0124] The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber;

[0125] Wherein, the immersion temperature is 50°C;

[0126] The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 50 minutes, then taken out of the furnace and cooled to room temperature.

[0127] The mass fraction of potassium hydroxide solution is 10%;

[0128] The mixing ratio of phenolic fiber and potassium hydroxide solution is 10g:100mL.

[0129] The heating rate is 10℃ / min;

[0130] The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

[0131] The mixing ratio of rosin resin and organic solvent is 35g:200mL;

[0132] The organic solvent is toluene.

[0133] The filler is calcium carbonate;

[0134] The antioxidant is antioxidant 1010;

[0135] S2 Melting:

[0136] The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid;

[0137] S3 Mixing:

[0138] Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

[0139] The stirring speed is 500r / min.

[0140] Example 4

[0141] A method for preparing a hot-melt waterproof adhesive for an optical cable comprises the following steps:

[0142] S1 Preparation:

[0143] Weigh the following components according to the mass ratio: 80 parts of butyl rubber, 11 parts of modified rosin resin, 2 parts of polymethyltriethoxysilane, 16 parts of filler, 1.8 parts of stearic acid, 7 parts of carbon black, 1.2 parts of polybutylene adipate, 1.1 parts of antioxidant, and 2.5 parts of nano-microcrystalline cellulose.

[0144] The preparation method of modified rosin resin is as follows:

[0145] Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber;

[0146] Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution;

[0147] Among them, the stirring speed is 200r / min;

[0148] The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion.

[0149] Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40;

[0150] Among them, the frequency of ultrasonic dispersion is 60kHz;

[0151] The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

[0152] The activated fiber preparation method is:

[0153] Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution;

[0154] The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber;

[0155] Wherein, the immersion temperature is 50°C;

[0156] The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 50-55 minutes, then taken out of the furnace and cooled to room temperature.

[0157] The mass fraction of potassium hydroxide solution is 10%;

[0158] The mixing ratio of phenolic fiber and potassium hydroxide solution is 11g:100mL.

[0159] The heating rate is 10℃ / min;

[0160] The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

[0161] The mixing ratio of rosin resin and organic solvent is 36g:200mL;

[0162] The organic solvent is toluene.

[0163] The filler is calcium carbonate;

[0164] The antioxidant is antioxidant 1010;

[0165] S2 Melting:

[0166] The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid;

[0167] S3 Mixing:

[0168] Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

[0169] The stirring speed is 500r / min.

[0170] Example 5

[0171] A method for preparing a hot-melt waterproof adhesive for an optical cable comprises the following steps:

[0172] S1 Preparation:

[0173] Weigh the following components according to the mass ratio: 81 parts of butyl rubber, 10 parts of modified rosin resin, 3 parts of polymethyltriethoxysilane, 18 parts of filler, 2 parts of stearic acid, 8 parts of carbon black, 1.5 parts of polybutylene adipate, 1.2 parts of antioxidant, and 3 parts of nano-microcrystalline cellulose.

[0174] The preparation method of modified rosin resin is as follows:

[0175] Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber;

[0176] Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution;

[0177] Among them, the stirring speed is 200r / min;

[0178] The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion.

[0179] Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40;

[0180] Among them, the frequency of ultrasonic dispersion is 60kHz;

[0181] The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

[0182] The activated fiber preparation method is:

[0183] Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution;

[0184] The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber;

[0185] Wherein, the immersion temperature is 50°C;

[0186] The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 55 minutes, then taken out of the furnace and cooled to room temperature.

[0187] The mass fraction of potassium hydroxide solution is 10%;

[0188] The mixing ratio of phenolic fiber and potassium hydroxide solution is 12g:100mL.

[0189] The heating rate is 10℃ / min;

[0190] The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

[0191] The mixing ratio of rosin resin and organic solvent is 40g:200mL;

[0192] The organic solvent is toluene.

[0193] The filler is calcium carbonate;

[0194] The antioxidant is antioxidant 1010;

[0195] S2 Melting:

[0196] The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid;

[0197] S3 Mixing:

[0198] Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

[0199] The stirring speed is 500r / min.

[0200] Comparative Example 1:

[0201] Based on Example 1, no modified rosin resin is added, and the rest of the technical solutions remain unchanged.

[0202] test:

[0203] The density of the sample was tested:

[0204] Table 1

[0205] <![CDATA[Density g / cm 3 > Example 1 1.02 Example 2 1.06 Example 3 1.08 Example 4 1.12 Example 5 1.07

[0206] It can be seen from Table 1 that the waterproof adhesive prepared by the present invention has a relatively suitable density and will not significantly increase the weight of the optical cable.

[0207] Inject waterproof glue into the copper core cable and conduct impact resistance test, refer to GB / T18480-2001, impact (falling weight height 150mm, 65kg):

[0208] Table 2

[0209] Impact resistance Example 1 No cracks, breaks or splits Example 2 No cracks, breaks or splits Example 3 No cracks, breaks or splits Example 4 No cracks, breaks or splits Example 5 No cracks, breaks or splits Comparative Example 1 Micro cracks, no breakage or cracking

[0210] It can be seen from Table 2 that the waterproof adhesive prepared by the present invention can effectively improve the impact resistance of the optical cable.

[0211] The voltage breakdown tester was used to inject the waterproof glue of the embodiment and the comparative example into the cable for testing:

[0212] Table 3

[0213] Breakdown voltage KV / mm Example 1 27.5 Example 2 28.3 Example 3 28.6 Example 4 28.1 Example 5 27.9 Comparative Example 1 24.2

[0214] It can be seen from Table 3 that the waterproof adhesive prepared by the present invention has excellent voltage breakdown resistance.

[0215] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A hot melt waterproof adhesive for optical cable, characterized in that: The invention comprises the following ingredients by weight: 60-85 parts of rubber, 10-12 parts of modified rosin resin, 1-3 parts of polymethyltriethoxysilane, 15-18 parts of filler, 1-2 parts of stearic acid, 5-8 parts of carbon black, 1-1.5 parts of polybutylene adipate, 1-1.2 parts of antioxidant and 2-3 parts of nano-microcrystalline cellulose.

2. The hot melt waterproof adhesive for optical cable according to claim 1, characterized in that: The modified rosin resin preparation method is: Firstly, the phenolic fiber is subjected to high temperature activation treatment to obtain activated fiber; Add rosin resin to an organic solvent, heat to 80°C, and stir for 40 minutes to obtain a rosin resin solution; Among them, the stirring speed is 200r / min; The activated fiber was added into the rosin resin solution and dispersed by ultrasound for 10 min to obtain a composite dispersion. Among them, the mixed mass ratio of activated fiber and rosin resin solution is 1:40; Among them, the frequency of ultrasonic dispersion is 60kHz; The composite dispersion is dried by rotary evaporation to obtain modified rosin resin.

3. The hot melt waterproof adhesive for optical cable according to claim 2, characterized in that: The activated fiber preparation method is: Add potassium hydroxide to water, and stir and mix at a speed of 100 r / min for 15 minutes to obtain a potassium hydroxide solution; The phenolic fiber is added into a potassium hydroxide solution, immersed for 4 hours, and then subjected to rotary evaporation drying to obtain a pretreated phenolic fiber; Wherein, the immersion temperature is 50°C; The pretreated phenolic fiber is placed in a carbonization furnace, heated to 620°C, kept warm for 50-55 minutes, then taken out of the furnace and cooled to room temperature.

4. The hot melt waterproof adhesive for optical cable according to claim 3, characterized in that: The mass fraction of the potassium hydroxide solution is 10%; The mixing ratio of phenolic fiber and potassium hydroxide solution is 10-12g:100mL.

5. The hot melt waterproof adhesive for optical cable according to claim 3, characterized in that: The heating rate is 10°C / min; The specific surface area of ​​the activated fiber is greater than 1300 m 2 / g, and the microporosity is greater than 92%.

6. The hot melt waterproof adhesive for optical cable according to claim 2, characterized in that: The mixing ratio of the rosin resin and the organic solvent is 30-40 g: 200 mL; The organic solvent is toluene.

7. The hot melt waterproof adhesive for optical cable according to claim 3, characterized in that: The filler is calcium carbonate; The antioxidant is antioxidant 1010; The rubber is butyl rubber.

8. The method for preparing a hot melt waterproof adhesive for optical cable according to claim 1, characterized in that: The following steps are involved: S1 Preparation: Weigh the components according to the mass ratio: rubber, modified rosin resin, polymethyltriethoxysilane, filler, stearic acid, carbon black, polybutylene adipate, antioxidant, nano-microcrystalline cellulose; S2 Melting: The rubber is added into a hot melting furnace, and then heated to 150°C at a heating rate of 20°C / min until the rubber is completely melted to obtain a rubber liquid; S3 Mixing: Modified rosin resin, polymethyltriethoxysilane, filler, and stearic acid were added to the rubber liquid in sequence and stirred for 20 minutes. Then, carbon black, polybutylene adipate, antioxidant, and nano-microcrystalline cellulose were added and stirred for 30 minutes to obtain a hot-melt waterproof adhesive.

9. The method for preparing a hot melt waterproof adhesive for optical cable according to claim 8, characterized in that: The stirring speed is 500 r / min.